Excessive training induces molecular signs of pathologic cardiac hypertrophy. Issue 11 (24th May 2018) - da Rocha, Alisson L.; Teixeira, Giovana R.; Pinto, Ana P.; de Morais, Gustavo P.; Oliveira, Luciana da C.; de Vicente, Larissa Gaioto; da Silva, Lilian E. C. M.; Pauli, José R.; Cintra, Dennys E.; Ropelle, Eduardo R.; de Moura, Leandro P.; Mekary, Rania A.; et al.
Abstract : Chronic exercise induces cardiac remodeling that promotes left ventricular hypertrophy and cardiac functional improvement, which are mediated by the mammalian or the mechanistic target of rapamycin (mTOR) as well as by the androgen and glucocorticoid receptors (GRs). However, pathological conditions (i.e., chronic heart failure, hypertension, and aortic stenosis, etc.) also induce cardiac hypertrophy, but with detrimental function, high levels of proinflammatory cytokines and myostatin, elevated fibrosis, reduced adenosine monophosphate‐activated protein kinase (AMPK) activation, and fetal gene reactivation. Furthermore, recent studies have evidenced that excessive training induced an inflammatory status in the serum, muscle, hypothalamus, and liver, suggesting a pathological condition that could also be detrimental to cardiac tissue. Here, we verified the effects of three running overtraining (OT) models on the molecular parameters related to physiological and pathological cardiac hypertrophy. C57BL/6 mice performed three different OT protocols and were evaluated for molecular parameters related to physiological and pathological cardiac hypertrophy, including immunoblotting, reverse transcription polymerase chain reaction, histology, and immunohistochemistry analyses. In summary, the three OT protocols induced left ventricle (LV) hypertrophy with signs of cardiac fibrosis and negative morphological adaptations. These maladaptations were accompanied by reductions in AMPKalpha (Thr172) phosphorylation, androgen receptor, and GR expressions, as well as by an increase in interleukin‐6 expression. Specifically, the downhill running–based OT model reduced the content of some proteins related to the mTOR signaling pathway and upregulated the β‐isoform of myosin heavy‐chain gene expression, presenting signs of LV pathological hypertrophy development. Abstract : (a) Overtraining protocols induced left ventricle hypertrophy with signs of cardiac fibrosis and negative morphological adaptations. (b) The downhill running–based overtraining model reduced the content of some proteins related to the mechanistic target of the rapamycin signaling pathway and upregulated the β‐myosin heavy‐chain gene expression.